Maximising utility savings through appropriate implementation of combined heat and power scheme - A. Manan, Zainuddin; Lim, Fang Yee (Penerbit UTM Press, 2004)

(untitled)
Combined Heat And Power (CHP) Scheme, Also Known As Cogeneration Is Widely Accepted As A Highly Efficient Energy Saving Measure, Particularly In Medium To Large Scale Chemical Process Plants. The Advantages Of A CHP Scheme For A Chemical Plant Are Two-Fold: (I) To Drastically Reduce Electricity Bill From On-Site Power Generation (Ii) To Save On Fuel Bills Through Recovery Of The Quality Waste Heat From Power Generation For Process Heating. In Order To Be Effective, A CHP Scheme Must Be Placed At The Right Temperature Level, In The Context Of An Overall Process System. Failure To Do So Might Render A CHP Venture Worthless. This Paper Describes The Procedure For An Effective Implementation Of A CHP Scheme Using An Ethyl Benzene Process As A Case Study. A Key Visualisation Tool In Pinch Analysis Technique Known As The Grand Composite Curve Is Used To Guide CHP Integration, And Allows It To Be Optimally Placed Within The Overall Process Scenario. The Study Shows That Appropriate CHP Integration With The Ethyl Benzene Process Above The Pinch Can Potentially Result In Significant Savings On Electricity Cost Of Up To 87%.